2008
DOI: 10.1002/dvdy.21499
|View full text |Cite
|
Sign up to set email alerts
|

Erasure of the paternal transcription program during spermiogenesis: The first step in the reprogramming of sperm chromatin for zygotic development

Abstract: Male germ cells possess a unique epigenetic program and express a male-specific transcription profile. However, when its chromatin is passed onto the zygote, it expresses an transcription/epigenetic program characteristic of the zygote. The mechanism underlying this reprogramming process is not understood at present. In this study, we show that an extensive range of chromatin factors (CFs), including essential transcription factors and regulators, remodeling factors, histone deacetylases, heterochromatin-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 44 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…During spermatogenesis, a complex interplay of histone posttranslational modifications (PTMs) take place in the nuclei of immature germ cells as they develop into mature spermatozoon (Chen et al, 1998;Godmann et al, 2007;Lewis et al, 2003;Payne and Braun, 2006;Rathke et al, 2013;Tachibana et al, 2007;van der Heijden et al, 2006;Zheng et al, 2008). Together with such histone PTMs, histone variants play a major role in the protamine transition and chromatin reorganization process during spermatogenesis, and many histone variants of histone H1 (H1t, H1T2 HILS1), H2A and H2B (TH2A, TH2B, ssH2B, H2A.B.bd, H2BL1, H2BL2, H2AL1-H2AL3) and H3 (H3t, H3.3) become expressed in specific germ cell types or are testes-specific (Lewis et al, 2003;Rathke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During spermatogenesis, a complex interplay of histone posttranslational modifications (PTMs) take place in the nuclei of immature germ cells as they develop into mature spermatozoon (Chen et al, 1998;Godmann et al, 2007;Lewis et al, 2003;Payne and Braun, 2006;Rathke et al, 2013;Tachibana et al, 2007;van der Heijden et al, 2006;Zheng et al, 2008). Together with such histone PTMs, histone variants play a major role in the protamine transition and chromatin reorganization process during spermatogenesis, and many histone variants of histone H1 (H1t, H1T2 HILS1), H2A and H2B (TH2A, TH2B, ssH2B, H2A.B.bd, H2BL1, H2BL2, H2AL1-H2AL3) and H3 (H3t, H3.3) become expressed in specific germ cell types or are testes-specific (Lewis et al, 2003;Rathke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In spermatogenesis, transcription is strongly activated during step 7 round spermatids, decreases sharply in 8, 9 step and at 10 step is undetectable (Zheng et al 2008). In sperm nuclear murine mRNA species, proteins are initially detected in step 7 round spermatids (Mali et al 1989), a stage corresponding to the T. tuberosum 21-days exposed group.…”
Section: Discussionmentioning
confidence: 99%
“…Mi et al (2007) observed in vitro that phenethyl isothiocyanate (PEITC) binds covalently to cellular proteins and induces apoptosis in cancer cell lines. Isothiocynates present in T. tuberosum could be acting on transcription regulatory, remodeling factors, histone deacetylases, heterochromatin binding proteins and/or topoisomerase in order to prevent gene transcription (Zheng et al 2008). Johns et al (1982) suggested that T. tuberosum has an estrogenic effect, however, sperm transport within and through epididymis is facilitated by the movements of efferent ducts epithelial cells cilia (Ilio & Hess 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This developmental process requires the zygotic genome activation (ZGA) to allow for the transition from specified germ cells to a totipotent embryo, in which both paternal and maternal genomes undergo dramatic epigenetic reprogramming regulated by maternal factors [3]. Overcoming chromatin-mediated transcriptional repression of paternal and maternal genomes is thought to be the first major step to initiate zygotic gene expression after fertilization [4][5][6][7][8][9].…”
Section: H33 Is Essential For Paternal Genome Activationmentioning
confidence: 99%
“…This developmental process requires the zygotic genome activation (ZGA) to allow for the transition from specified germ cells to a totipotent embryo, in which both paternal and maternal genomes undergo dramatic epigenetic reprogramming regulated by maternal factors [3]. Overcoming chromatin-mediated transcriptional repression of paternal and maternal genomes is thought to be the first major step to initiate zygotic gene expression after fertilization [4][5][6][7][8][9].The mammalian sperm genome is packaged into highly condensed chromatin consisting primarily of protamine but 5-15% residual histones. Following fertilization, ZGA occurs first in the paternal genome (male pronucleus) at the 1-cell stage embryo, while activation of the maternal genome is usually delayed and occurs at the 2-cell stage in mice [10][11][12][13].…”
mentioning
confidence: 99%